Verbal politeness strategies in the Philippines motivations for indirectness, politeness or both? - Huggins, Jacqueline (Philippine Journal of Linguistics, 2014)
Politeness strategies in speech acts has generated considerable research and debates especially concerning the notions of directness and indirectness as compared to Westerners who are considered more direct while Asians more indirect. Researchers have suggested that distinctions signal degrees of politeness; consequentially, Westerners appear less polite and Asians more polite (Sifianou 1997:46). However, researchers have found varying degrees of directness and indirectness among Western and Asian cultures (Rundquist 1992). Some research questions whether indirectness is linked to politeness. This paper, as an aid for cross-cultural workers, discusses politeness in communication charting specific examples comparing American English and Philippine English to indicate how comparable expressions of greetings, requesting, asking questions, and expressing gratitude may be considered polite in one variety of English, yet impolite in another. Verbal strategies with a focus on indirectness are also presented using Brown and Levinson’s (1978/1987) four types of politeness strategies: bald on-record, negative politeness, positive politeness, and off-record.​